The learning potential of streaming media: cultural sustainability in a post-digital society - Heuman, Johannes; Rampazzo Gambarato, Renira (Frontiers in Communication, 2023)
The aim of this article is to contribute to a discussion on the challenges of and opportunities for using major streaming media platforms and fictional streaming series in an educational context. The article departs from research on the post-digital condition, platformization, cultural memory, and cultural sustainability. The tangible interest in cultural memory and heritage studies indicates the current need to include streaming services in these research fields, as the platforms for streaming media are vectors of popular culture and heritage in terms of digital archives. With the help of Astrid Erll's analytical model, the authors argue that perspectives from cultural memory studies are useful for deepening the learning potential of fictional series on streaming platforms. The article also supports the idea that major streaming services can be used in education as a supplement to other cultural resources if the potential sustainability risks are considered.